Intention model and factors leading to MSMEs falling into the trap of illegal online loans - Farida, Lilik; Saleh, Chairul; Indraningrat, Ketut; Utami, Elok Sri; Apriliana, Tria (Universitas Negeri Surabaya, Indonesia, 2025)
The micro, small, and medium enterprises (MSMEs) sector in Indonesia plays a vital role in the economy and job creation, but often struggles with limited access to capital. As a result, many MSMEs turn to fintech solutions or online loans, including illegal ones, which usually trap them in high-interest debt. Factors influencing this behaviour include social norms, perceived behavioural control, financial literacy, risk perception, interest rates, social influence, perceived ease of use, perceived usefulness, trust in illegal loans, education level, and social media usage for advertising. At the same time, the Financial Services Authority (OJK) are working to reduce MSMEs’ involvement with illegal online loans. This research aims to examine the factors that drive MSMEs to use illegal loans, focusing on how trust in online loans and the intention to use them mediate this behaviour. Additionally, education level and frequency of social media use are examined as moderating factors. The study surveyed 330 MSMEs and analysed the data using structural equation modelling. The findings indicate that subjective norms significantly increase trust in illegal loans but do not significantly impact the intention to use them. Perceived behavioural control influences both trust and the intention to use illicit loans. Interest rates also have a significant positive effect on both trust and intention. Social influence increases trust but decreases the intention to use illegal loans. Lastly, the intention to use illicit loans strongly predicts actual behaviour, with education level reinforcing this link, while frequent social media use weakens it.